2011
DOI: 10.1016/j.freeradbiomed.2011.08.016
|View full text |Cite
|
Sign up to set email alerts
|

Sleep deprivation under sustained hypoxia protects against oxidative stress

Abstract: We previously showed that total sleep deprivation increased antioxidant responses in several rat brain regions. We also reported that chronic hypoxia enhanced antioxidant responses and increased oxidative stress in rat cerebellum and pons, relative to normoxic conditions. In the current study, we examined the interaction between these two parameters (sleep and hypoxia). We exposed rats to total sleep deprivation under sustained hypoxia (SDSH), and compared changes in antioxidant responses and oxidative stress … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 42 publications
1
15
0
Order By: Relevance
“…6) among which 7 protein showed level increase. This is in agreement with previous examinations and theories, that concluded antioxidant responses after sleep deprivation, as a consequence of the higher metabolic rate related to prolonged wakefulness (Reimund, 1994; Brown and Naidoo, Ramanathan et al, 2010;Ramanathan and Siegel, 2011). This result draws attention on a high level of impairment in the oxidative homeostasis which is even more pronounced later after sleep deprivation termination.…”
Section: The Importance Of the Most Abundant Functional Clusters Of Ssupporting
confidence: 92%
“…6) among which 7 protein showed level increase. This is in agreement with previous examinations and theories, that concluded antioxidant responses after sleep deprivation, as a consequence of the higher metabolic rate related to prolonged wakefulness (Reimund, 1994; Brown and Naidoo, Ramanathan et al, 2010;Ramanathan and Siegel, 2011). This result draws attention on a high level of impairment in the oxidative homeostasis which is even more pronounced later after sleep deprivation termination.…”
Section: The Importance Of the Most Abundant Functional Clusters Of Ssupporting
confidence: 92%
“…On the other hand, to block SWS, it was found that the most reported protocol is the total sleep deprivation (TSD) procedure [ 29 , 36 , 38 , 39 , 53 55 ]. The TSD data is summarized in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
“…For example, 12 articles of mice under PSD procedures [ 27 , 40 , 41 , 43 – 47 , 49 52 ] and 13 papers of rats after PSD methods [ 28 , 30 35 , 37 , 42 , 48 , 56 58 ] were analyzed. However, TSD protocols were described exclusively in rats [ 29 , 36 , 38 , 39 , 53 55 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Suppression of firing of hippocampal pyramidal cells by lactate has been attributed to changes in redox status (Gilbert et al, 2006 ). Enforced wakefulness is characterized by a significant oxidative burden relative to sleep (Silva et al, 2004 ; Cirelli, 2006 ; Ramanathan et al, 2010 ; Ramanathan and Siegel, 2011 ). Manipulation of oxidative stress-related pathways affects sleep wake cycles (Honda et al, 1994 ; Inoué et al, 1995 ; Kimura et al, 1998 ; Ikeda et al, 2005 ).…”
Section: Discussionmentioning
confidence: 99%